2016
DOI: 10.1080/14786419.2016.1146886
|View full text |Cite
|
Sign up to set email alerts
|

Noralashinol A, a new norlignan from stem barks of Syringa pinnatifolia

Abstract: One new norlignan, namely noralashinol A (1), one known analogue (2), together with seven known lignans (3-9) were isolated from the stem barks of Syringa pinnatifolia. Their structures were elucidated extensively by spectroscopic methods, including mass spectrometry and 1D and 2D NMR spectroscopies. Compound 8 significantly inhibited NO production in LPS-induced BV-2 murine microglia cells with its IC50 value of 20.7 μM, compared to a positive control quercetin with its IC50 value of 15.3 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Unlike the lignans and iridoidal glycosides reported from the bark of SP, sesquiterpenoids are rarely reported. Notably, sesquiterpenoids have not been described from any other species in the Oleaceae family. ,, The in vitro bioassays explored the protective effects of these compounds toward H9c2 cells against hypoxia-induced injuries and their NO inhibitory effects in RAW264.7 cells, which were valuable for identifying the anti-AMI components of SP. These findings provide a foundation for the clinical use of SP against coronary diseases in traditional medicine.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the lignans and iridoidal glycosides reported from the bark of SP, sesquiterpenoids are rarely reported. Notably, sesquiterpenoids have not been described from any other species in the Oleaceae family. ,, The in vitro bioassays explored the protective effects of these compounds toward H9c2 cells against hypoxia-induced injuries and their NO inhibitory effects in RAW264.7 cells, which were valuable for identifying the anti-AMI components of SP. These findings provide a foundation for the clinical use of SP against coronary diseases in traditional medicine.…”
Section: Resultsmentioning
confidence: 99%
“…Especially 9-norlignans (lacking carbon 9 from the parent lignan skeleton) with guaiacyl (3-methoxy-4-hydroxyphenyl) moieties have rarely been reported in the literature, although they would be expected to be common norlignans as guaiacyl lignans are the most abundant class of lignans. To the best of our knowledge, (+)-imperanene, vitrofolal E and F, noralashinol A and C are the only guaiacyl type 9-norlignans which have been reported as plant constituents [1,2,3,4]. The unnatural enantiomer, (−)- R -imperanene, dehydroxyimperanenes and dihydrodehydroxy-imperanenes have also been synthesized [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…According to the definition above, approximately 25 naturally occurring 9-norlignans can be found in the literature. These are yateresinol ( 1 ) [8], pachypostaudin A and B ( 2 , 3 ) [9], aglacin H ( 4 ) [10], vitrofolal A,B,E, and F ( 5 , 6 , 7 , 8 ) [2,11] descuraic acid ( 9 ) [12], cestrumoside (glycoside) ( 10 ) [13], (−)-justiflorinol ( 11 ) [14], (+)-virgatyne ( 12 ) [15], the arylnaphthalene derivative 13 [16] and the lactone 14 [17] , compound 15 [18], S -(+)-imperanene ( 16 ) [1], 3-methoxy-imperanene ( 18 ) [19], noralashinol A and C ( 19 , 20 ) [3,4], tectonoelin A and B ( 21 , 22 ) [20], peperotetraphin ( 23 ) [21] the related cyclobutane carboxylates 24 and 25 [22] and hyperione A and B ( 26 , 27 ) [23] (Figure 2). In addition, some related 9-norlignans have been synthesized and some 9-norlignan like compounds have also been reported [6,24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peeled twigs, stems, and roots of SP, with Chinese name ‘Shan‐Chen‐Xiang’, have been used for treatment of cardiovascular symptoms, asthma, and pains in Mongolian medicine for a long history [3] . Previous chemical studies demonstrated that SP is mainly constituted by lignans as major amount and a few content of sesquiterpenoids [4–7] . Pharmacological investigations demonstrated that SP volatile oil [8] or EtOH extract [9–11] showed anti‐acute myocardial ischemia (AMI) in vivo .…”
Section: Introductionmentioning
confidence: 99%